Teachers’ Personal Competence and Students’ Learning Motivation in Study English on Luring Learning Model During Pandemic Covid-19: A Correlational Study - Hakim, M. Arif Rahman; Sulastri, Vira; Andriadi; Astari, Ade Riska Nur; Rahimi, Mahmood (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This study aims to determine the correlation between the teachers’ personal competence and students’ learning motivation. This research employs a quantitative, correlational method. The study's population comprised all students from Madrasah Aliyah Pancasila Bengkulu, with a total sample size of 66 students from 3 classes. The research and calculation results indicate that the personal competence of the teachers at MA Pancasila Bengkulu meets the